Combined medical imaging with CFD analysis for application of diagnostic and treatment planning: The case study of human nasal airflow simulation based on CT imaging - Hemtiwakorn, Khaisang; Phoocharoen, Niwat; Tungjitkusolmun, Supan; Mahasittiwat, Visan; Sangworasil, Manas; Pintavirooj, Chuchart (My University, 2009)
The previous methods of human airflow measurement such as rhinomanometry or acoustic rhinometry could not visualize the airflow and calculated the velocity magnitude in specific region of nasal cavity. Thus, this study proposes the combination of CT and CFD analysis of nasal airflow simulation in normal human breathing. This method can demonstrate the airflow direction, and also calculate the velocity magnitude inside the nasal cavity. The processes of this study are segmentation, meshing, solving, and post-processing. Firstly, Mimic 10.01 software was used to segment the nasal cavity. Secondly, Pro-STAR/amm software was used to generate trimmed mesh of 338, 496 elements. Finally, computational grid model was imported to STAR-CD version 3.26 for numerical computation, and visualize the solution by post-processing. The result shows that velocity magnitude of airflow is greatest in nasal valve area which is the narrowest area of the human nose. Also, the flow commonly pass through the main nasal passage and middle meatus areas of nose. Experimental validation will be reported in the further publication. In conclusion, this study is the important begining of an applied CFD analysis with medical imaging. CT imaging combines with CFD analysis could be useful for rhinologist as a nose function evaluation technique. Moreover, the applications of this method could be utilized in a wide range of research topics, especially development of diagnostic and treatment planning techniques.
Keywords: CFD; CT; Nasal model